Renewal Plan and Reform State Educational Programme in Relation to the Perspective of Technical Education in Primary Schools in Slovakia - Pavelka, Jozef (The University of Rzeszów Publishing House, 2023)
The study is based on selected parts of the Renewal Plan – Component 7: Education for the 21st Century, outlining the main aims and objectives of curriculum reform for primary and secondary education in Slovakia. The reform is set to be fully implemented from 2026. In relation to the aims and objectives of the curriculum reform, the study presents analytical conclusions regarding possible problem areas related to technical education in primary schools.
Keywords: technical education; primary school; curriculum reform; problematic areas